2012
DOI: 10.1093/humrep/des012
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative pregnancy rate after ICSI-IVF in patients with colorectal endometriosis: results of a multicentre study

Abstract: Our data confirm that ICSI-IVF offers a high CPR per patient. However, determinant factors of CPR should be taken into account when informing couples of their options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(110 citation statements)
references
References 37 publications
4
101
1
4
Order By: Relevance
“…Previous studies [37,44] have reported a lower PR in women with endometriosis associated with adenomyosis. However, these authors did not distinguish between external and internal adenomyosis or between diffuse and focal adenomyosis.…”
Section: Limiting Factors When Evaluating Fertility In Women With Colmentioning
confidence: 69%
See 3 more Smart Citations
“…Previous studies [37,44] have reported a lower PR in women with endometriosis associated with adenomyosis. However, these authors did not distinguish between external and internal adenomyosis or between diffuse and focal adenomyosis.…”
Section: Limiting Factors When Evaluating Fertility In Women With Colmentioning
confidence: 69%
“…Moreover, in accordance with a previous study [35], no difference in PR was noted between women with colorectal endometriosis and those with tubal or male infertility. Subsequently, in a multicenter study including the women from Mathieu d'Argent et al's series, Ballester et al [37] showed that the cumulative PRs after one and two IVF-ICSI cycles were 29.3 and 52.9%, respectively. In this specific setting, we are currently waiting for the results of an ongoing trial comparing first-intention MAR and colorectal surgery in women with patent fallopian tubes and without associated male infertility to build a therapeutic strategy.…”
Section: Fertility After Mar In Women With In Situ Colorectal Endometmentioning
confidence: 99%
See 2 more Smart Citations
“…Dies verdeutlicht, dass die Ansprüche an die Patientinnenselektion für eine Operation und die Qualität der Operation entscheidende Erfolgsfaktoren sind. Natür-lich beeinflussen weitere Faktoren wie Alter, Serum-AMH-Spiegel und das Vorhandensein anderer Begleitfaktoren die Prognose entscheidend [2]. Somit wird jeder einzelne Fall eine individuelle Betrachtung und Beratung erfordern.…”
Section: Heterogenität Des Endometriosekollektivsunclassified